Consumer Protection Against The Rampant Circulation of Cosmetics Without Bpom Permission In The Practice of Buying and Selling In E-Commerce - Januartha, I Putu Gede Bisma; Widyantara, I Made Minggu (Dinasti Research, 2024)
The aim of this research is to determine the legal protection sought for consumers purchasing cosmetics against the widespread distribution of cosmetics without BPOM permission in e-commerce. The method used in this research is a normative legal research method with a statutory regulatory approach. The research results show that consumers who experience losses due to purchasing fake beauty products have legal protection as regulated in Law no. 8 of 1999 concerning Consumer Protection (UUPK). Regarding legal protection for consumers who experience losses due to the use of cosmetics, producers are obliged to provide compensation (restitution) to consumers in accordance with the provisions in Article 19 paragraphs (1) and (2) UUPK. Regarding the role of the Food and Drug Supervisory Agency (BPOM) in monitoring illegal cosmetics, BPOM has carried out supervision through an online site, namely cyber patrol. Apart from that, to ensure the authenticity of cosmetic products, you can check them online using an application or by scanning a barcode. This process involves checking the product name, dosage form, registrant name, and registration number.